2016
DOI: 10.1007/s10815-016-0721-5
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation in the luteal phase: systematic review and meta-analysis

Abstract: Purpose The purpose of this study was to evaluate whether outcomes are different if controlled ovarian stimulation (COS) is started in the luteal phase rather than the follicular phase. Methods A systematic review and meta-analysis was performed. Sixteen studies were included in the qualitative analysis, and eight studies with a total of 338 women were included in the quantitative analysis. Results Cycles initiated in the luteal phase were slightly longer (WMD 1.1 days, 95 % CI 0.39-1.9) and utilized more tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The number of retrieved oocytes in the LPS was similar to that of the FPS. This result was consistent with the findings reported in previousstudies . A previous study showed that there was no elevated rate of abnormality at birth after LPS compared to FPS .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The number of retrieved oocytes in the LPS was similar to that of the FPS. This result was consistent with the findings reported in previousstudies . A previous study showed that there was no elevated rate of abnormality at birth after LPS compared to FPS .…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with the findings reported in previousstudies. 15,16 A previous study showed that there was no elevated rate of abnormality at birth after LPS compared to FPS. 17 Another study showed that euploid blastocyst rate calculated either per biopsied blastocyst or injected MII oocyte was not significantly different between FPS and LPS groups.…”
Section: Fps (N = 29) Lps (N = 21) Pmentioning
confidence: 96%
“…Pituitary function is suppressed by the continuous supply of progestin during PPOS . It was reported that a dose of 10 mg of medroxyprogesterone acetate (MPA) per day could effectively inhibit spontaneous ovulation in both the natural cycle and in cycles of ovarian stimulation .…”
Section: Introductionmentioning
confidence: 99%
“…The drugs that are used to inhibit the spontaneous luteinizing hormone surge include not only the conventional GnRH antagonists, but also medroxyprogesterone acetate. 27 In a recent meta-analysis of a total of 338 women who | 359 TAKAI underwent ovarian stimulation (251 of whom did so for fertility preservation) that began in the luteal phase, 28 the duration and dosage of the FSH preparations were significantly higher than in a control group of women, in whom ovarian stimulation was initiated in the early follicular phase. However, there were no significant differences in the number of retrieved oocytes, cryopreserved embryos, or peak estradiol levels.…”
Section: Random-start Protocolmentioning
confidence: 99%
“…These findings suggest that in random-start protocols, ovarian stimulation lasts 1-2 days longer, resulting in an increase in the dosage of the fertility drugs; however, the number of retrieved oocytes is similar to the number that is retrieved with the conventional protocol. For the ovarian stimulation of infertile women that was initiated in the luteal phase, the pregnancy rate that was achieved with cryopreserved embryos was reported to be similar to the rates for conventional ovarian stimulation 28 ; however, there are currently few studies featuring a comparison of pregnancy rates between the random-start and conventional stimulation protocols and no study of the pregnancy rates in women who are undergoing ovarian stimulation for fertility preservation.…”
Section: Random-start Protocolmentioning
confidence: 99%